2022
DOI: 10.31557/apjcp.2022.23.11.3673
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Educational Intervention on Junior Dentists’ Capacity to Detect Oral Mucosal Lesions and Suspect Malignant Potential

Abstract: Objectives: This study aimed to assess the impact of Continuing Education (CE) activity on junior dentists' competency to identify oral mucosal abnormalities those suggestive of oral cancer or potentially malignant disorders. Materials and Methods: This multiphase study administered a pre-validated quiz to dental interns and junior dentists. The quiz was designed to assess the respondent's competency to recognize different oral lesions and stratify their potential for malignancy. Invited candidates attempted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Concerning OPMDs, the scenario was more surprising, where no difference in diagnostic accuracy was reported between practising dental health professionals and final-year dental students. The trend of incompetency in detecting OPMDs is a historical issue in the literature, where previous studies reported diagnostic accuracies of up to 40% (Gaballah et al, 2021;Gaballah & Kujan, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Concerning OPMDs, the scenario was more surprising, where no difference in diagnostic accuracy was reported between practising dental health professionals and final-year dental students. The trend of incompetency in detecting OPMDs is a historical issue in the literature, where previous studies reported diagnostic accuracies of up to 40% (Gaballah et al, 2021;Gaballah & Kujan, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning OPMDs, the scenario was more surprising, where no difference in diagnostic accuracy was reported between practising dental health professionals and final‐year dental students. The trend of incompetency in detecting OPMDs is a historical issue in the literature, where previous studies reported diagnostic accuracies of up to 40% (Gaballah et al, 2021; Gaballah & Kujan, 2022). Likewise, a previous comparative study that used clinical images for diagnosis found low and comparable results between dental students and general dental practitioners regarding OPMD diagnostic accuracy, ranging between 32% and 35% (Gaballah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations